The Case of This War of Mine: A Production Studies Perspective on Moral Game Design. Issue 4 (June 2019) - de Smale, Stephanie; Kors, Martijn J. L.; Sandovar, Alyea M.
This article reports on a study with 11 bit studios and their game, This War of Mine . Rather than a formal analysis of the game, our objective was to situate the research in game production studies by documenting the design context (gamework) and designer perceptions about the game that inform morally complex gameplay. The research was conducted with four team members of 11 bit studios: a senior game designer, a writer, a senior writer (with stakes in marketing), and a quality assurance lead. We employed reflective interviewing techniques and visual methods to better understand how moral gameplay was designed. Our analysis illustrates the roles underlying narratives in the design process and balancing everyday work negotiations play in the design of moral gameplay, how a designer's research informs the vision to create emotional realism in the game, and the importance of a player-centered iterative design process to produce morally engaging gameplay.